2008
DOI: 10.1161/strokeaha.107.500603
|View full text |Cite
|
Sign up to set email alerts
|

New Brain Lesions After Carotid Stenting Versus Carotid Endarterectomy

Abstract: New DWI lesions occur more frequently after CAS than after CEA. However, technical advances mainly in the field of endovascular therapy potentially reduce the incidence of these adverse ischemic events. In this scenario, DWI appears to be an ideal tool to compare and further improve both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
234
5
30

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(288 citation statements)
references
References 62 publications
19
234
5
30
Order By: Relevance
“…[1][2][3][4] This has led to the development and widespread application of cerebral protection devices. 5,6 The most widely used devices are those based on distal filter placement that capture emboli dislodged from plaque; however, their application may result in additional complications.…”
mentioning
confidence: 99%
“…[1][2][3][4] This has led to the development and widespread application of cerebral protection devices. 5,6 The most widely used devices are those based on distal filter placement that capture emboli dislodged from plaque; however, their application may result in additional complications.…”
mentioning
confidence: 99%
“…This rate is lower than that of previous studies (28,29). A previous meta-analysis found a significantly lower incidence (33%) of new periprocedural ischemic lesions in protected patients than in unprotected patients (45%) (29).…”
Section: Outcome Based On Carotid Hr-mri Findingsmentioning
confidence: 54%
“…Several investigators, using DWI to detect clinically silent embolic lesions after protected CAS, have reported new DWI lesions at frequencies of 6.7-73 % [8,[17][18][19][20][21]. A substudy of the International Carotid Stenting Study (ICSS) reported that new DWI lesions occurred in 62 of 124 patients (50 %) in the stenting group [18].…”
Section: Discussionmentioning
confidence: 99%